A Study of the State Bank of India's Performance Using the CAMELS Method of Analysis - Dr. Ahmad Khalid Khan; Dr. Syed Mohammad Faisal (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
When judging the current state of the economy, it is essential to consider how vital the financial sector is to boost economic activity. It is crucial to the operation of an economy's banking system, which includes monetary and fiscal systems, all of which rely on how well that economy's banking system performs. We will use the CAMELS approach of analysis to the gathered data to evaluate the performance of the State Bank of India. The Reserve Bank of India was the first institution to suggest the CAMELS Rating System. The authors used data from reliable secondary sources for the SBI from 2012 to 2022 to conduct their study. The years 2012 through 2022 saw the utilization of this data. This research employed an OLS regression model to examine the variables' unit roots and the data's normality. This was done to find out what kind of relationship there is between the dependent variable and the other variables. The financial standing of models representing the performance of the banking sector is examined using the CAMELS analysis technique. These prototypes are used to explore the financial performance of the archetypes of Indian financial institutions that make up the banking industry. This investigation's primary target, the State Bank of India, can render a decision. The data provided in this study also helps future researchers comprehend how the CAMELS Approach impacted the effectiveness and profitability of financial organizations. Future researchers will have access to this study's financial measurements and the CAMELS Method, which may be used to assess the overall financial health of institutions. The links to these two contributions are provided below.